Refugee Crisis, News Crisis: The Framing of Episodic and Thematic Articles - Keith Joseph Zukas; Panagiotis P. Liapis (Athens Journal of Mass Media and Communications, 2024)
A main tenet of 21st Century journalism is to engage the public with highly informative and affective content. Through sociological journalistic processes of creating news content, however, audiences may lose the ability to completely conceptualize the level of human suffering observed in the coverage of refugee crises. This experimental survey tested the use of episodic and thematic frames in formatting American news articles about the Syrian refugee crisis of migrants landing on Grecian shores. It found that episodically framed articles increased moral understanding among Americans, as well as overall engagement in the crisis event. Respondents, however, were not more likely to participate in civic engagement about the refugee crisis with others. The results suggest that the use of episodic frames in the construction of refugee news articles may engage audiences more in the issue, however, alone are not enough to affect behavioral outcomes such as discussion. Further research should investigate the implications of framing choices made in the presentation of news stories about important issues such as mass human migrations.